Genetically Modified Language : The Discourse of Arguments for GM Crops and Food - Cook, Guy (New York Routledge, an imprint of Taylor & Francis Group, 2005)
Written in a clear style and drawing on illustrative examples, Genetically Modified Language is an insightful look at how language shapes our opinions. Cook subjects the language of the case for GM to a careful and detailed examination and demonstrates that language which purports to seek clarity actually manipulates opinion.
Include Appendices, Notes, Bibliography and Index.
The Discourse of Arguments for GM Crops and Food.
Keywords: Transgenic plants -- Discourse analysis -- Genetically modified foods -- Crops--Genetic engineering -- Food--Biotechnology